Thermal stability of lead-halide perovskites in perovskite solar cells - Tay, Darrell Jun Jie (Nanyang Technological University, 2025)
Of the various third-generation solar cell technologies, lead-halide perovskite-based solar cells have achieved power efficiencies rivalling that of traditional silicon-based solar cells. This has spurred attempts to commercialise this new technology. However, thermal stability remains an unresolved issue for lead-halide perovskites, which impede their use in commercial applications. Elevated temperatures cause the perovskite structure to break down, and the material loses the property to absorb light efficiently. Thus, methods to stabilise the perovskite structure are necessary for eventual commercialisation. Compositional variation offers one pathway to attaining thermally stable perovskite films, although the current literature is shrouded in contradictions. One example is the effect of varying the FA+/MA+ ratio and Cs+/FA+ ratio in mixed FA-MA perovskites and Cs-FA perovskites respectively. Another example is the lack of empirical knowledge, such as that of all-inorganic caesium lead iodide. In addition, various claims, some untested and some contradictory, have been put forth in an attempt to explain the thermal stability of these perovskites, such as morphological issues, or defect densities. The composition of the perovskite is the most fundamental component of the perovskite solar cell to design and alter. Therefore, it is of utmost importance to look into the thermal stability trends of perovskites with these A-site cations, as well as to assess these claims on the other factors, to ensure that the intrinsic thermal stability of the perovskite film is as high as possible, before consideration of its use in devices.